2018
DOI: 10.53956/jfde.2018.120
|View full text |Cite
|
Sign up to set email alerts
|

Plurilingualism in Teaching and Learning: Complexities Across Contexts

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Kubota's critique of plurilingualism echoes Cenoz's (2009) study which shows translanguaging can be considered simultaneously as a threat to the survival of minority languages or as an opportunity for their development (Choi & Ollerhead, 2018).…”
Section: Plurilingualism In Higher Education Institutionsmentioning
confidence: 92%
“…Kubota's critique of plurilingualism echoes Cenoz's (2009) study which shows translanguaging can be considered simultaneously as a threat to the survival of minority languages or as an opportunity for their development (Choi & Ollerhead, 2018).…”
Section: Plurilingualism In Higher Education Institutionsmentioning
confidence: 92%
“…Previous research investigating the student perspective revealed their preference toward an environment that makes use of their HL(s) (Hall and Cook, 2012;Choi and Ollerhead, 2018;Shin et al, 2020;Wernicke et al, 2021). In fact, as research studies have demonstrated, students have been particularly adamant about the positive impact that HL use can bring to a lesson while they have also been able to pinpoint specific classroom strategies that could have benefited from HL integration.…”
Section: The Positive Impact Of Students' Hl(s) In the Classroommentioning
confidence: 99%
“…According to Wernicke et al (2021), attention should be paid to multilingualism and multiculturalism in educational settings to increase awareness and recognition of linguistic and cultural diversity at individual and societal levels. Further, research articulated that historical, ideological, social, economic, and political factors need to be taken into consideration, as well as language policy and the diverse language practices of teachers and students (Choi and Ollerhead, 2018). Multilingual education presupposes not only the teachers' proficiency in several languages (Nunan and Lam, 1998) but also their knowledge and understanding of language acquisition processes, theoretical and pedagogical models, approaches focused on the development of multilingual competence (Hammond, 2014), teaching strategies, language and content integration (Palincsar and Schleppegrell, 2014), and language policies and ideologies related to language teaching and language use (Flores and Rosa, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, research has emerged on the implementation of translanguaging pedagogy in the United States (Garcı ´a et al 2015;Pacheco et al 2015;Garcı ´a and Kleyn 2016;Garcı ´a et al 2017;Pacheco 2018;Davila 2019;Menken and Sanchez 2019;Seltzer 2020) and other parts of the world (Paulsrud et al 2017;Svensson 2017;St. John 2018;Choi and Ollerhead 2018;Gynne 2019;Ollerhead 2019;Carbonara and Scibetta 2020).…”
Section: Studies Of Multilingual Classroom Interaction and Agencymentioning
confidence: 99%